Europium(III) Diphenylphosphinate 1D1 Structures: Coordination Polymers as Nanothermometers for Wide Temperature Ranges - da Motta, Vinícius Rodrigues [UNESP]; Bim, Luís Felipe Bricks [UNESP]; Scarpari, Sergio Luis [UNESP]; Stucchi, Elizabeth Berwerth [UNESP]; Cebim, Marco Aurélio [UNESP] (Springer Nature, 2025)
In this work, a new ratiometric sensor for nanothermometry is proposed, based on the coordination polymer [Eu(dpp)3]n – europium(III) diphenylphosphinate – in which the compound’s multicentric emissions are used to determine the absolute temperature across a wide range, from cryogenic temperatures (–100 °C) up to 200 °C. The compound was prepared by wet route precipitation synthesis, resulting in one-dimensional cylindrical particles that can be classified as nanorods or nanowires, with a length-to-diameter ratio greater than 10. The high chemical and thermal stability of the compound allows its use in this temperature range. Thermogravimetric analysis showed its decomposition to europium(III) polymetaphosphate, followed by the formation of europium(III) orthophosphate, with diphenylphosphinate ligands starting to decompose at 450 °C. FT-IR revealed at least two different types of coordination of the diphenylphosphinate ligands to the EuIII ions, corroborating the presence of more than one EuIII center in the asymmetric unit of the coordination polymer. The [Eu(dpp)3]n exhibits an excitation spectrum primarily dominated by ligand excitation, with charge transfer and intraconfigurational transitions of EuIII showing lower intensity. Two types of transition are observed in the emission spectrum: one associated with a high-symmetry site and the other with low-symmetry sites. These emission bands were deconvoluted in the spectrum. The intensity ratio between emissions of the high and low symmetry sites was used as the luminescent intensity ratio (LIR), demonstrating through the analysis of the thermometric parameter as a function of temperature that the energy levels of the two EuIII centers are thermally coupled. Finally, the relative sensitivity of the thermometers was calculated, yielding a value of 0.98% K−1 at 172.65 K.
Keywords: Coordination polymers; Lanthanoids; Luminescence spectroscopy; Nanothermometry; Nanowires; Rare earth metals